Songs for the brokenhearted : a novel - Tsabari, Ayelet, 1973- (Random House, 2024)
"1950. Thousands of Yemeni Jews have immigrated to the newly founded Israel in search of a better life. In an overcrowded immigrant camp in Rosh Ha'ayin, Yaqub, a shy young man, happens upon Saida, a beautiful girl singing by the river. In the midst of chaos and uncertainty, they fall in love. But they weren't supposed to; Saida is married and has a child, and a married woman has no place befriending another man. 1995. Thirty-something Zohara, Saida's daughter, has been living in New York City-a city that feels much less complicated than Israel, where she grew up wishing her skin were lighter, her illiterate mother's Yemeni music quieter, and that the father who always favored her was alive. She hasn't looked back since leaving home, rarely in touch with her mother or sister, Lizzie, and missing out on her nephew Yoni's childhood. But when Lizzie calls to tell her their mother has died, she gets on a plane to Israel with no return ticket. Soon Zohara finds herself on an unexpected path that leads to shocking truths about her family-including dangers that lurk for impressionable young men and secrets that force her to question everything she thought she knew about her parents, her heritage, and her own future"--